Paper tube nursery technique in Cotton:Timely establishment and enhanced yield - Sankaranarayanan, K; Prakash, A H (Indian Farming, 2022)
Transplanting of cotton has many advantages includes reduces main field duration, maintaining of plant population, manipulate the time of sowing to achieve optimum time, fitting crop into low length of growing period region, advantage in cropping system by reducing main field duration,Â and also suitable for the farm has undesirable quality of irrigation water for germination. Paper tube Nursery techniqueÂ was developed by following vigorous testingÂ proceduresÂ during the year ofÂ 2013-14 andÂ Â 2014-15 at Central Institute for Cotton Research, Regional Station, Coimbatore . SubsequentlyÂ field trial was conducted duringÂ 2015-16 . The field experiment wasÂ attemptedÂ with two method of planting (transplanting and direct sown) andÂ threeÂ planting times Â (27th August, 15th September (late planting) , andÂ 5th October (late planting).The seedling at the age of 21 days was transplanted. The interaction results revealed that 25th August transplanting registered 15.34 percent higher seed cotton yield as compared to corresponding date of direct sown cropÂ . However 5th October transplanting registered enhanced performance of 64.7 percent higher seed cotton yield as compared to corresponding date of direct sown crop. The results revealed that 25th August transplanting realized 4.8% higher net return but transplanting of 15th September arrived as 44.4Â Â per cent of higher net return as compared to direct sown of same date respectively. The results concluded that the visible advantage of transplanting observed in late sown situations.